Identification of genetic variants in five chinese families with keratoconus: Pathogenicity analysis and characteristics of parental corneal topography - Cheng, Wan-Yu; Yang, Shang-Ying; Huang, Xiao-Yu; Zi, Fei-Yin; Li, Hui-Ping; Sheng, Xun-Lun (Frontiers in Genetics, 2022)
Purpose: The study aims to identify genetic variants in five Chinese families with Keratoconus (KC) and describe the characteristics of parental corneal topography. Methods: Fifteen participants, including five probands and ten parents from five Chinese families with KC, were recruited for genetic and clinical analyses. Targeted next-generation sequencing using a custom-designed panel for KC was applied on the probands for variant identification. Sanger sequencing and cosegregation analysis of the suspected pathogenic variants were performed on the family members. The pathogenicities of variants were evaluated according to the American College of Medical Genetics and Genomics guidelines (ACMG). Pentacam 3D anterior segment analysis system was applied for keratectasia detection and the Corvis ST for corneal biomechanics measurement. Fifteen parameters were recorded, including nine keratectasia indicators (BAD-D, TP, Kmax, Df, Db, Dp, Dt, Da, ARTH), six corneal biomechanical indicators (CBI, DA ratio, SP-A1, IR, bIOP, TBI). Results: A total of six novel variants, including five missense variants and one frameshift variant, were detected in the HMX1, SLC4A11, TGFBI, PIKFYVE, and ZEB1 genes in five probands, all of which showed co-segregation of genotype and clinical phenotype and were determined to be pathogenic. The genetic model was autosomal dominant (AD) in four families and autosomal recessive (AR) in 1 family. The analysis of keratectasia and corneal biomechanical indicators of the proband’s parents (first-generation relatives) in AD families revealed that there were several abnormal indexes in BAD-D, TP, Kmax, Df, Db, Dp, Dt, Da, CBI, DA ratio, SP-A1, IR, bIOP and TBI test indexes, showing clinical characteristics of incipient KC. Conclusion: Our study shows that variants in HMX1, SLC4A11, TGFBI, PIKFYVE, and ZEB1 were associated with KC. Our study extends the gene spectrum associated with KC, provides novel insights into KC phenotypic assessments, and contributes to early diagnosis for these patients.